Influence of short-term follow-up on cardiovascular risk status among high-risk hypertensive patients in Turkey: an observational study - Omer Kozan; Rıskman Study Group (KARE Publishing, 2016)
Objective: The present study was designed to evaluate clinical practice of cardiovascular (CV) risk management and the influence of follow-up on risk profile among hypertensive patients. Methods: Of the 1023 patients enrolled in the cross-sectional phase, data from 397 high-risk patients (mean [SD] age, 59.2 [11.5] years; 62.5% female) who had attended at least 1 follow- up visit within 9 months of (longitudinal phase) enrollment were included in the present non-interventional study of CV risk factors, 10-year coronary heart disease (CHD) risk estimate, risk level, and risk management. Results: Ten-year CHD risk (p<0.001), and percentages of patients with high risk (20.7 vs 13.4%) and very high risk (19.6 vs 6.6%) significantly decreased upon follow-up (p<0.001). Significant reductions in systolic and diastolic blood pressure (BP), and low-density lipoprotein (LDL) cholesterol (p<0.001 for each), and an increase in high-density lipoprotein (HDL) cholesterol (p=0.007) were associated with a positive shift in risk grouping (42.8%). The shift toward lower-risk grouping was more prominent in patients with diabetes (5.5% vs 41.1%) and metabolic syndrome (19.2% vs 34.2%; p<0.001 for each). Achievement of target BP significantly improved upon follow-up, particularly in lower-risk groups (p<0.001). Conclusion: Results indicate better CV risk management in hypertensive patients, with a pronounced decrease in 10- year CV risk estimate and a switch to lower-risk grouping, particularly in patients with diabetes mellitus and metabolic syndrome, associated with close follow-up.